The Effect of Project Based Learning Model Assisted by Learning Management System on Biography Text Writing Skills of Grade X High School - Turnip, Maraman Rotua; Murtadho, Fathiaty; Yarmi, Gusti (Journal of Educational Sciences, 2025)
This study aims to evaluate the influence of the project-based learning (PjBL) model supported by the learning management system (LMS) on the writing skills of biographical texts of high school students in class X in Kelapa Gading, North Jakarta. LMS-assisted PjBL is expected to replace the monotonous conventional method. The method used is quantitative with a quasi-experimental design, namely pretest-posttest control group design. The results of the study showed that the average score of students reached 87, higher than the pretest, with a completion percentage of 100%. The improvement in the comprehension of biographical texts in the experimental class reached 86.56%, and the score between pretest and posttest increased by 19 points. The hypothesis test with the t-test showed α < 0.05, so H1 was accepted, signaling a significant difference between the control and experimental classes. Of the 67 students in the experimental class, 57 students did not complete the pretest, but after treatment, the average post-test score reached 82 with 100% completeness. The normality and homogeneity test showed normal and homogeneous distribution. The final results showed an increase in biographical text writing skills by 62.68% with the application of the LMS-assisted PjBL model.